Answer:
![Ka=([SO_3]^2)/([O_2]^3) \\\\Kb=([SO_3]^3)/([SO_2][O_2]^(1/2))](https://img.qammunity.org/2022/formulas/chemistry/college/d4fgx70wu6djl681rw4u1cnltvwl7r53gv.png)
Step-by-step explanation:
Hello!
In this case, according to the reactions:
a.) 2 S(s) 3 O2(g) ⇔ 2 SO3(g) Ka
b.) SO2(g) + 1/2 O2(g) ⇔ SO3(g) Kb
Thus, according to the law of mass action, we can write Ka and Kb as follows:
![Ka=([SO_3]^2)/([O_2]^3) \\\\Kb=([SO_3]^3)/([SO_2][O_2]^(1/2))](https://img.qammunity.org/2022/formulas/chemistry/college/d4fgx70wu6djl681rw4u1cnltvwl7r53gv.png)
Whereas solid carbon is not inserted in the equilibrium expression.
Best regards!